SOCIAL AND HYGIENIC FACTORS AFFECTING PATIENTS WITH CHRONIC HEPATITIS - Jalolov N. N. (The Conference Hub, 2025)
The scientific article presents a deep analysis of the socio-hygienic factors affecting patients with chronic hepatitis. Hepatitis B and C are among the most serious infectious diseases that threaten the lives of millions of people worldwide. The study selected the following indicators as the main evaluation criteria: patients' living conditions, sanitary and hygienic culture, drinking water quality, nutritional status, bad habits (alcohol, smoking, injection drug use), level of medical culture, and activity of seeking help from health care institutions. The study assessed the impact of socio-hygienic conditions on the course of chronic hepatitis based on sociological surveys, medical and sanitary analysis, statistical analysis, and health reports.
Keywords: Chronic hepatitis, socio-hygienic factors, WHO statistics, hepatitis B, hepatitis C, healthy lifestyle, sanitation, hygiene, disease prevention, health care.